Developing online learning video based on the science technology society (STS) to improve biology learning outcomes - Tuti Handayeni; I Putu Artayasa; Dewa Ayu Citra Rasmi (Jurnal Pijar Mipa, 2021)
This research aims to determine the validity of online learning video based on the Science Technology Society (STS) and its effect on biology learning outcomes at SMA Negeri 1 Labuapi. The type of research is research and development with the ADDIE model. The research sample was class X students at SMA NegeriÃÂ  1 Labuapi with as many as 12 students for the control class and 15 students for the experimental class. Research data obtained from learning outcomes tests (post-test scores) on environmental change material. The results of data analysis showed that the level of validity of the developed video obtained a percentage of 84% in terms of media which include very valid criteria and 86% in terms of material which include very valid criteria. The results of data analysis of learning outcomes data showed that there was a difference in the average post-test score between the experimental class through the application of learning using video which combined with the STS approach and the control class through the application of conventional learning. The average score of the post-test in the experimental class was 84.23, while the average score of the post-test in the control class was 67.17. The significance value of two independent sample t-test obtained is 0.002, the significance value obtained is smaller than 0.05 (p-value < 0.05), so Ho is rejected. The conclusion of this research that the video developed has very valid criteria and the application of learning using video based on the science technology society (STS) approach has a significant effect on improving biology learning outcomes at SMA Negeri 1 Labuapi.